К теории параметрической устойчивости - Мартынюк, А.А.; Хорошун, А.С. (Видавничий дім "Академперіодика" НАН України, 2007)
A general method of analysis based on Lyapunov's direct method is presented for studying the parametric stability of the nonlinear systems of differential equations. The results demonstrate the roles played by (1) estimating the domain of potential asymptotic stability and (2) constructing the auxiliary Lyapunov function.